Effects of Active‐Site Modification and Quaternary Structure on the Regioselectivity of Catechol‐O‐Methyltransferase. Issue 8 (21st January 2016) - Law, Brian J. C.; Bennett, Matthew R.; Thompson, Mark L.; Levy, Colin; Shepherd, Sarah A.; Leys, David; Micklefield, Jason
Abstract: Catechol‐ O ‐methyltransferase (COMT), an important therapeutic target in the treatment of Parkinson's disease, is also being developed for biocatalytic processes, including vanillin production, although lack of regioselectivity has precluded its more widespread application. By using structural and mechanistic information, regiocomplementary COMT variants were engineered that deliver either meta ‐ or para ‐methylated catechols. X‐ray crystallography further revealed how the active‐site residues and quaternary structure govern regioselectivity. Finally, analogues of AdoMet are accepted by the regiocomplementary COMT mutants and can be used to prepare alkylated catechols, including ethyl vanillin. Abstract : Old cat, new tricks : Protein engineering of catechol‐ O ‐methyltransferase generated mutants with improved regioselectivity, thus enabling meta ‐ or para ‐methylation of substrates in significant regioisomeric excess. X‐ray crystal structures elucidate the role of active‐site residues and quaternary structure on enzyme regioselectivity. A one‐pot tandem enzyme reaction was developed to regioselectively alkylate catechols by using AdoMet analogues.